The distribution of aerobic bacteria in Chinese cropland is linked to the soil texture - Xiao Jiamin; Wu Haonan; Xu Chao; Hu Yajun; Xu Zhiwen; Zhang Dongxu; Li Abo; Li Abo; Wei Xiaomeng; Ge Tida; Wei Gehong (Frontiers in Microbiology)
Aerobic bacteria extensively drive the carbon cycle in soil owing to their vigorous respiration; however, their geographical distribution and mechanisms remain poorly understood. The citric acid synthetase-encoding gene (gltA), which encodes the key enzyme in the tricarboxylic acid cycle of aerobic respiration, was used as a marker gene to investigate the geographical distribution of aerobic bacteria in Chinese agricultural fields. The abundance and diversity of gltA-harboring bacteria changed unimodally as the latitude increased, with peak values at middle latitudes, where the dominant species showed the lowest relative abundance. Despite the different water management practices, our data found little difference in the abundance, diversity, or relative abundance of the dominant species of gltA-harboring bacteria between paddy and upland soils on a large scale, which was significantly affected by the soil type (black, fluvo-aquic, and red), which can be defined by the soil texture. Linear regression and random forest model analyses indicated that soil texture strongly regulated the community of gltA-harboring bacteria, particularly the abundance of this functional guild. Generally, less abundant and diverse gltA-harboring bacteria were observed in soils with higher clay content. We identified biomarkers in the different soil types using linear discriminant analysis effect size analysis. The results suggest a significant correlation between soil texture and most of these biomarkers. Additionally, the biomarkers in black soil were mainly r-strategists, which include Proteobacteria, Actinobacteria, and Bacteroidetes, were positively correlated with soil organic carbon content. In contrast, the biomarkers in fluvo-aquic soil were generally K-strategists, such as Acidobacteria, Ktedonobacteraceae, Planctobacteriaceae, and Frankia were negatively correlated with soil organic carbon content. These different biomarkers likely play distinct roles in soil carbon sequestration. This study provides foundational insights into the role of aerobic bacteria in soil and enhances our understanding of microbial contributions to the biogeochemical cycle of carbon.